ANALISIS DAN PERANCANGAN SISTEM AKUNTANSI PERSEDIAAN PADA UD LI JAYA KUPANG - Asnat C Bani Bili; R E H Riwumanu; Ari Data (Journal of Management Small and Medium Enterprises (SMEs), 2020)
Inventory is a large asset owned by the company. Large investments invested in the form of inventory willcause problems related to the cost of organizing where the cost will increase the warehouse costs. Inventoryis very vulnerable to damage, theft, and misappropriation. The inventory accounting system plays animportant role in the arrangement of avoiding the repatriation of the company's wealth, especiallyinventory. Proper and correct accounting treatment of inventory is absolutely necessary. This is becausethe inventory post has a considerable influence in the financial statements, which is in the balance sheetand in determining the price of inventory in the income statement. The problem in the research is how todesign good documents, records, and procedures related to the inventory accounting system ofmerchandise at Usaha Dagang Li Jaya Kupang and how the internal control system prevent the multipositions, mis-recording, and possible misappropriation of inventory of at Usaha Dagang Li JayaKupang. The results showed that the inventory accounting information system at UD. Li Jaya hasweaknesses in terms of inventory recording undone because of the limited educational background of theexisting workforce and in terms of its internal controls that have not been effective. The obstacles faced byUD. Li Jaya Kupang is the absence of computerized administration in the recording system, so that isno recording at all in the warehouse section. The inventory accounting information system at UD LiJaya Kupang must have its own recording administration, so that employees do not record bythemshelves. Keywords : Inventory, Intenal Control, Inventory Accounting Information System